Parathalestris clausii ... - Apostolov, Apostol (Zenodo, 2014)
Parathalestris clausii (Norman, 1869) Material examined: St.12 (5 ♀♀). Rinsing macroalgae Fucus vesiculosus Linnaeus, 1753. Distribution in Iceland: Icelandic shore of the Atlantic Ocean. ... : Published as part of Apostolov, Apostol, 2014, Contribution to the study of marine harpacticoid fauna (Crustacea, Copepoda) of Iceland, pp. 1-5 in ZooNotes 62 (62) on page 3, DOI: 10.5281/zenodo.8298375 ...